Wsparcie społeczne w roli zasobu obniżającego poziom stresu odczuwanego przez matki dzieci z niepełnosprawnością intelektualną = Social support in the role of a resource to reduce the level of stress experienced by mothers of children with intellectual disabilities - Ratajczak, Ewa; Janiszewska-Nieścioruk, Zdzisława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text presents a study that aimed to establish the relationship between social suport and the level of stress experienced by mothers of children with intellectual disabilities. Thus, it was concluded that parents and especially mothers, due to the burdens associated with the process of diagnosis, upbringing and rehabilitation of a child with a disability, experience stress in a special way, which should be reduced by the support available and diverse in its offer - psycho-emotional, socialservice, care and rehabilitation. At the same time, it is advisable that its scope or dimension, as well as the time of its provision, be systematically monitored. This increases its adequacy and effectiveness, which is conducive to reducing the stress felt by mothers of children with intellectual disabilities.
Keywords: wsparcie społeczne; stres odczuwany przez matki dzieci z niepełnosprawnością intelektualną; social support; stress experienced by mothers of children with intellectual disabilities